Cytotoxic Phenolic Compounds from Fruit Glandular Trichomes of Macaranga tanarius - Thi Mai Huong Doan; Thuy Linh Nguyen; Thi Thanh Van Trinh; Van Nam Vu; Thi Dao Phi; Marc Litaudon; Fanny Roussi; Van Minh Chau; Van Cuong Pham (Journal of Analytical Methods in Chemistry)
A new flavonoid, macatanarin D (1), together with five known stilbenes (2-6), was isolated from fruit glandular trichomes of Macaranga tanarius. Their structures were elucidated on the basis of spectroscopic methods and through comparison with data reported in the literature. All isolated compounds were evaluated for their cytotoxic activities against KB and MCF-7 cell lines. Compounds 3, 4, and 5 showed the strongest activities against both cell lines with IC50 values in the range of 0.03–0.12 μM, and compound 2 only showed a significant cytotoxicity against KB cell line (IC50 = 0.26 μM) and a moderate cytotoxicity against MCF-7 (IC50 = 10.4 μM). Compounds 1 and 6 showed weak cytotoxic activities against KB cell line with IC50 values of 29.3 and 24.7 μM, respectively.